Inorganic chromium(III) compounds - Santonen, Tiina (World Health Organization, 2009)
Inorganic Chromium (III) Compounds provides summaries of the relevant scientific information concerning the potential effects of these chemicals upon human health and/or the environment. Chemical safety cards on the most common inorganic trivalent chromium compounds are reproduced in this document.
Concise international chemical assessment document ; 76
Keywords: environmentální vědy; vystavení vlivu životního prostředí; Toxicity Tests; Maximum Allowable Concentration; hodnocení rizik; sloučeniny chromu; maximální přípustná koncentrace; Environmental Exposure; testy toxicity; Chromium Compounds; Risk Assessment